TOGA education: Introduction of eco orphanage concept in Bekonang, Sukoharjo - Efri Roziaty; Santhyami Santhyami; Ima Aryani; Annur Indra Kusumadani; Sudrajah Warajati Kisnawaty; Alden Ganendra Madhava Priya Hardianto; Fito Zuhud Abdillah (Community Empowerment, 2024)
The community service was conducted at the Putri Aisyiyah Orphanage in Bekonang, Sukoharjo, Central Java. This orphanage has yard space that has not been utilized for Family Medicinal Plants (TOGA) and is not yet familiar with the concept of an eco orphanage. The main objective of this service is to provide education about TOGA to the children at the Putri Aisyiyah Bekonang Orphanage. The service activities comprise six phases: pre-test, socialization, TOGA planting, practices in processing traditional medicinal products, post-test, and maintenance and supervision. The outcomes of the service activities include the planting of twenty types of medicinal plants in the orphanage's yard. Participants' knowledge increased after receiving education about TOGA, encompassing basic knowledge of TOGA (12.4%), types of TOGA and their characteristics (38%), and the health benefits of TOGA (33%). There was an enhancement in participants' knowledge regarding the types and benefits of TOGA, with an average total increase of 27.7%. Thus, this service has succeeded in providing education about TOGA to the children at the Putri Aisyiyah Bekonang Orphanage and enhancing their understanding of the types of TOGA and their health benefits.